Impact of Transcranial Direct Current Stimulation on Reading Skills of Children and Adolescents With Dyslexia. (3rd October 2018) - Rios, Débora Medeiros; Correia Rios, Mino; Bandeira, Igor Dórea; Queiros Campbell, Fernanda; de Carvalho Vaz, Daniel; Lucena, Rita
Introduction: Rehabilitation techniques have been used to facilitate reading acquisition in dyslexia. However, many individuals continue to present academic impairment throughout life. New intervention strategies are necessary to further help this population. Objectives: Assess the impact of transcranial direct current stimulation on reading skills in children and adolescents with dyslexia. Methods: The study was conducted with one-group pretest–posttest. Participants received 2 mA transcranial direct current stimulation during 30 minutes for 5 consecutive days. Reading performance was measured by a group of tasks (identification and reading of letters, syllables, words, nonwords, and text). Results: A significant increase in the number of correct answers for nonwords and text tasks was observed after transcranial direct current stimulation ( P = .035 and P = .012, respectively). Conclusion: The transcranial direct current stimulation seems to be a promising tool for the treatment of reading problems in dyslexia. Future studies are necessary to confirm the effects of transcranial direct current stimulation and to establish optimal intervention protocol in this population.